THE ANALYSIS OF MATHEMATICAL PROOF ABILITY - Siti Hardianti; Thamrin Tayeb; Fitriani Nur; Ahmad Farham Majid; Baharuddin Baharuddin (MATEMATIKA DAN PEMBELAJARAN, 2020)
The ability to prove mathematically is one of the important abilities in learning mathematics. This study aims to determine students' mathematical proof ability. This type of research is a qualitative descriptive study, which involved 38 sixth semester students of the Mathematics Education Department, Tarbiyah and Teacher Training College, Alauddin Makassar State Islamic University with 3 of them being interview subjects. The instruments and data collection techniques used were researchers using diagnostic tests and interview guides. The analysis techniques used are data reduction, display data, and conclusion drawing / verification. The result of this research is that the students' mathematical proving ability in working on the questions is not optimal. In the indicator of the ability to construct evidence, students are less able to make connections between known facts and the elements to be proven. Furthermore, on the indicator of the ability to read a proof, students are less able to use definitions as a basis for providing arguments.